Unearthing the response pattern of COVID-19 research in social sciences. Issue 5 (6th July 2021) - Singh, Vibhav; Verma, Surabhi
Abstract : Purpose: The sudden onset of COVID-19 has brought about a watershed moment in the current research across all disciplines. As it has impacted almost all aspects of human existence, academicians are aggressively trying to understand the phenomenon from multidisciplinary perspectives. In this regard, the present study attempts to provide an in-depth understanding of academia's response pattern in the field of social sciences using a grounded theory literature review and bibliometric analysis. Design/methodology/approach: The present study analyzed 395 research articles on the pandemic phenomenon, yielding five main themes and 11 sub-themes. Findings: The emergent research themes are global impact on public health, the influence of COVID-19 on workplace functioning, global governance in COVID-19, research ethics in scholarly works and the influence of COVID-19 on demography. Originality/value: Drawing from these themes, the authors provide propositions, policy implications and future research directions.